Design and deposition of single and multilayer antireflection coatings of glass substrate using electron beam deposition. (2018) - Sharma, Nancy; Kumar, Mukesh; Kumari, Neelam; Karar, Vinod; Sharma, Amit L
Abstract: E-beam deposition technique offers many advantages compared to other physical vapour deposition techniques in terms of film uniformity, reproducibility and its optical efficiency. In the present work, design and deposition of both single and multilayer antireflection filter has been performed on optical grade glass substrates. Materials for coating were selected on basis of literature review consisting mainly of oxides and fluorides. Thickness of individual layers was optimized using Filmstar TM software for both single and multilayer antireflection coating. The performance of coatings was characterized using various spectroscopic techniques such as UV–Vis spectrophotometer and Gonio spectrophotometer. The peak transmittance was found to be 96.41% for single layer and 94.09% for multilayer antireflection coatings respectively. The performances for both antireflection coatings are compared and analyzed for best possible results. These filters can be used for applications such as transparent industrial display systems, relay optics in complex optical instruments and can further be customized for solar cell application.